Medium-term temporal stability of the helminth component community structure in bank voles (Clethrionomys glareolus) from the Mazury Lake District region of Poland - Bajer, Anna; Behnke, Jerzy M.; Pawelczyk, Agnieszka; Kulis, Karolina; Sereda, Michal J.; Sinski, Edward (Cambridge University Press, 2005)
The structure of helminth communities in wild rodents is subject to seasonal variation, and is dependent on host age within years. Although between-year variation has been monitored, seldom has it been assessed rigorously by appropriate multifactorial analysis with potentially confounding factors taken into account. In this study we tested the null hypothesis that despite seasonal, host age and sex effects, helminth communities should show relative stability between years. Over a period of 3 years (1998–2000) we sampled bank vole (Clethrionomys glareolus) populations (total n=250) at 2 points in the year: in spring, at the start of the breeding season, and in autumn, after the cessation of breeding. In spite of seasonal differences and strong age effects, the between-year effects were surprisingly small. Measures of component community structure (Berger- Parker dominance index, the dominant species, S. petrusewiczi) did not vary, or varied only slightly from year to year. The majority of measures of infracommunity structure [Brillouin’s index of diversity, prevalence of all helminths combined, prevalence and abundance of H. mixtum (the most prevalent helminth), mean species richness] did not differ significantly between years when other factors such as age, sex and seasonal variation had been taken into account. Some between-year variations were found (at the component community level, Simpson’s index of diversity ; at the infracommunity level, prevalence and abundance of S. petrusewiczi and abundance of all helminths combined), but even these were modest in comparison to seasonal and age differences, and were primarily attributable to S. petrusewiczi. We conclude that despite dynamic within-year fluctuations, helminth communities in bank voles in this region of Poland show relative stability across years. The sporadic occurrence of individual platyhelminths at low prevalence, makes little difference to the overall structure, which is largely maintained by the key roles played by the dominant intestinal nematodes of bank voles and the rarer species collectively.